MARKET MIX FACTORS AFFECTING THAI TOURISTS’ DECISION TO USE SMALL AND MEDIUM-SIZED HOTELS UNDER THE CRITICAL CONDITIONS OF THE COVID-19 PANDEMIC IN CHIANG MAI, THAILAND - qun, liao; LEELAPATTANA, Winitra; TRAKANSIRIWANICH, Keerati; WAIAPHA, Yutthakarn; SITTHIKUN, Suthira (Asian Administration and Management Review, 2022)
Due to the COVID-19 epidemic situation, tourist behavior has changed, Therefore, this research aims to study the behavior of Thai tourists and marketing mix factors affecting the decision to use the service of medium and small-sized hotels of Thai tourists under the critical condition of COVID-19 epidemic in Mueang District, Chiang Mai Province. The result of the study found that the majority of Thai tourists staying in hotels visited the hotel during holiday season and their stay in the hotel, they prefer to choose Standard Rooms, due to their affordable price. Before booking, they have study and read reviews from online media, they already knew the hotel from online media sources such as Websites/Facebook/IG/Tiktok, etc. Market mix factors affecting Thai tourists’ decision to use small and medium-sized hotels under the critical conditions of the COVID-19 pandemic found that, overall, market mix factors influence tourists’ decision to use small and medium-sized hotels at 84.0%. In terms of employee factors, it affects the decision to choose their service, followed by the service process and the physical aspect, respectively.